ERRORS BETWEEN MALE AND FEMALE STUDENTS IN CHANGING ACTIVE TO PASSIVE VOICE - Ravena Tania; Ardayati; Yulfi (LP3MKIL, 2022)
Abstract This research aimed to analyze errors in order to obtain kinds, differences and causes of error between male and female students in changing active to passive voice. Sample of this research was the twelfth grade students of SMA Negeri 5 Lubuklinggau. The method of the research was qualitative descriptive research. The researcher used test and interview as the technique to collect the data. In analyzing the data, the researcher used four steps were: first, collecting the data, second is identifying the data, third, describing data and finally, the researcher explains the data. The results showed that there are four kinds of error made by male students in changing active to passive are; Misformation errors with 68.84%, Misordering 21.34% Omission 8.70%, and Addition 0.72%. On the other hand, there are only 3 kinds of error made by female students are; Misformation error 53.47%, Misordering 29.37%, Omission 17.16%. From the result of written test, the differences between male and female students in changing active to passive voice is male students tend to make more error than female students. In addition, the researcher found three causes of error made by male and female students in this analysis namely; interlingual transfer, intralingual transfer and communication strategies. In conclusion, this research showed that there are 4 kinds of error and 3 causes of errors between male and female students, and male students tend to make more errors than female students in changing active to passive voice. Keywords: Error Analysis, Female, Male, Passive Voice.